Willful Ignorance and Epistemic Virtues: Education for Critical Epistemic Character - Grušovnik, Tomaž (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
One of the main challenges for the “Information-deficit model,” a mainstream theory in science communication, is motivated avoidance of information. A part of this is also willful ignorance, questioning “knowledge transfer” as the traditional educational model, since ignorance is often not a consequence of a lack of information but avoidance of knowledge. This means that caring about the development of critical thought should also entail a special education of mind that can apprehend unpleasant conclusions. The hypothesis that the present chapter offers implies that we should commit to virtue epistemology and the education of epistemic character with the emphasis on epistemic courage and curiosity.